The rationale of rationalization. (2020) - Veit, Walter; Dewhurst, Joe; Dołęga, Krzysztof; Jones, Max; Stanley, Shaun; Frankish, Keith; Dennett, Daniel C.
Abstract: While we agree in broad strokes with the characterisation of rationalization as a "useful fiction, " we think that Fiery Cushman's claim remains ambiguous in two crucial respects: (1) the reality of beliefs and desires, that is, the fictional status of folk-psychological entities and (2) the degree to which they should be understood as useful. Our aim is to clarify both points and explicate the rationale of rationalization.